A selective ammonia leaching process for high-calcium copper mine tailings
Patent Information
- Application Number
- CN202611383694.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本发明的目的在于提供一种高钙铜矿尾砂的选择性氨浸出工艺,解决现有技术在处理高钙铜矿尾砂时酸浸选择性差、结垢严重,以及氨浸浸出率偏低、浸出渣未资源化的问题
1、高选择性浸出:在碳酸铵-氨水弱碱性体系中,铜以铜氨络离子的形式选择性溶出,铜浸出率在70%以上;而钙几乎不浸出,从根本上避免了酸浸工艺中硫酸钙结垢、设备堵塞、酸耗大等系列问题。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hydrometallurgical technology, specifically relating to a selective ammonia leaching process for high-calcium copper ore tailings. Background Technology
[0002] Copper mine tailings are a large amount of industrial solid waste generated during copper mining and beneficiation. my country's annual copper mine tailings discharge is approximately 30 million tons, with accumulated stockpiles exceeding 300 million tons. Long-term accumulation not only occupies significant land resources but also easily leads to ecological and environmental problems such as heavy metal migration. Currently, the mainstream technologies for extracting valuable copper from copper mine tailings include acid leaching and ammonia leaching.
[0003] Acid leaching process: Strong acids such as sulfuric acid, hydrochloric acid or nitric acid are used as leaching agents to dissolve copper through the reaction of hydrogen ions with copper tailings. However, it has significant drawbacks. For high-calcium copper tailings (calcium content can reach 25-35%), a large amount of calcite (CaCO3) will be dissolved, resulting in: (1) extremely high calcium ion concentration in the leaching solution, which can reach tens of thousands of mg / L. In the sulfuric acid system, calcium sulfate scale is easily generated, which can clog pipes and equipment; (2) a large number of impurity ions are dissolved simultaneously, which increases the difficulty of subsequent separation and purification; (3) high acid consumption and high cost; (4) severe equipment corrosion.
[0004] Ammonia leaching process: Ammonia water and ammonium salts are used as leaching agents, and the leaching occurs through a copper-ammonia coordination reaction [Cu(NH3)4]. 2+ Selective leaching of copper is achieved, with almost no leaching of impurity elements such as calcium. It has the advantages of good selectivity, fewer impurities, and less equipment corrosion. However, the existing ammonia leaching technology still has the following shortcomings: (1) The leaching rate needs to be improved. Conventional ammonia leaching usually has a copper leaching rate of 50-70% for low-grade copper ore tailings, which still has room for improvement; (2) The leaching residue is not utilized. Most processes only focus on copper extraction and often simply pile up or landfill the leaching residue, which cannot achieve full resource utilization; (3) Existing technologies often introduce external physical fields such as ultrasound for enhancement. For example, in the CN121428287A patent that our team has previously disclosed, although the leaching rate is high, it requires additional ultrasound equipment, which increases investment and energy consumption. Summary of the Invention
[0005] The purpose of this invention is to provide a selective ammonia leaching process for high-calcium copper ore tailings, solving the problems of poor acid leaching selectivity, severe scaling, low ammonia leaching rate, and lack of resource utilization of leaching residue in existing technologies for treating high-calcium copper ore tailings. This invention achieves highly selective copper extraction by optimizing the ammonia leaching system without the need for external physical fields such as ultrasound. Simultaneously, the leaching residue can be directly used to prepare building materials without complex pretreatment, achieving full resource utilization of copper ore tailings.
[0006] This invention adopts an integrated process route of "selective leaching of ammonium carbonate, leaching enhanced by imidazole ionic liquid / AEO surfactant → solid-liquid separation → copper recovery from leaching solution → direct building material application of leaching residue". The core is: (1) using an ammonium carbonate-ammonia water system to selectively leach high-calcium copper ore tailings, so that copper is in the form of [Cu(NH3)4] 2+ (1) The form enters the solution, while the phases such as calcium carbonate are retained; (2) The imidazole ionic liquid / AEO surfactant is compounded to further improve the leaching rate; (3) The leaching parameters are determined to achieve high copper leaching without external physical field; (4) Since the leaching residue retains components such as calcium carbonate and silicon dioxide, it can be directly used as building material raw material without complicated pretreatment.
[0007] A selective ammonia leaching process for high-calcium copper ore tailings includes the following steps: Step 1: Grind the high-calcium copper ore tailings to obtain powder; Step 2: Add the powder, imidazole ionic liquid and AEO surfactant to the leaching agent, stir and leach, separate the solid and liquid to obtain leachate and leaching residue.
[0008] Leaching mechanism: In the weakly alkaline ammonium carbonate-ammonia water system, copper undergoes a coordination reaction with ammonia molecules to form a stable water-soluble copper-ammonia complex ion [Cu(NH3)4]. 2+ This selectively transfers copper from the solid phase to the liquid phase. Simultaneously, because the system pH is controlled at a weakly alkaline level, calcite (CaCO3) hardly dissolves (the reaction CaCO3 + 2H+ ions / mL → ... + →Ca 2+ +CO2↑+ H2O requires acidic conditions), and the calcium ion concentration in the leachate is extremely low (≤10mg / L), thus avoiding scaling problems.
[0009] Special note: Unlike the leaching residue produced by acid leaching process, the leaching residue obtained by this invention retains components such as calcium carbonate, and its calcium-silicon ratio is more suitable for direct use in the production of building materials, without the need for additional calcium supplementation or complex chemical conditioning treatment.
[0010] As a preferred embodiment of the present invention, in step 1, the calcium content of the high-calcium copper ore tailings is not less than 25 wt% and the copper content is not more than 1 wt%.
[0011] In a preferred embodiment of the present invention, in step 2, the solid-liquid ratio of the powder and the leaching agent is 1 g: 2-6 mL; the mass of the imidazole-based ionic liquid is 0.02-0.06% of the mass of the powder; and the mass of the AEO-based surfactant is 0.02-0.1% of the mass of the powder. This solid-liquid ratio range ensures good solid-liquid mass transfer and a suitable copper concentration.
[0012] Preferably, the solid-liquid ratio of the powder and the leachate is 1g:4mL.
[0013] In a preferred embodiment of the present invention, in step 2, the imidazole-based ionic liquid is at least one of 1-octyl-3-methylimidazolium chloride, 1-decyl-3-methylimidazolium chloride, and 1-dodecyl-3-methylimidazolium chloride; the AEO-based surfactant has an average EO addition number of 8-10. AEO-based surfactants exhibit good stability in ammonium carbonate-ammonia mixed leaching agents, and the EO segments are key structures for maintaining their hydrophilicity and interfacial activity. Controlling the average EO addition number to 8-10 can significantly reduce the interfacial tension between high-calcium copper ore tailings and the leaching agent, enhancing the leaching effect and making it easier for the leaching agent to reach and fully contact the active sites of copper, thereby increasing the leaching rate. Too low an average addition number leads to insufficient hydrophilicity and weakened dispersion ability; too high an average addition number weakens the adsorption effect and reduces the leaching aid effect. The anions and cations of imidazole ionic liquids can affect interfacial properties through non-covalent interactions such as electrostatics, hydrogen bonding, and adsorption. Appropriate addition can improve the mass transfer environment, reduce the resistance to copper migration into the liquid phase without interfering with the copper-ammonia complexation reaction, and especially improve the leaching of deep copper.
[0014] In a preferred embodiment of the present invention, in step 2, the leaching agent is an ammonium carbonate-ammonia water mixed leaching agent; the ammonium carbonate concentration of the ammonium carbonate-ammonia water mixed leaching agent is 1.5-3.5 mol / L, and the pH is 8.5-10.5. Too low an ammonium carbonate concentration results in insufficient leaching rate, while too high a concentration increases costs without significant benefit. A suitable pH ensures the stability of copper-ammonia complexes, calcium carbonate, etc.
[0015] Preferably, the ammonium carbonate concentration of the ammonium carbonate-ammonia water mixed leaching agent is 2.5 mol / L and the pH is 9-9.5.
[0016] In a preferred embodiment of the present invention, in step 2, the stirring leaching temperature is 20-60℃, the stirring rate is 200-400 rpm, and the time is 2-6 hours. Increasing the temperature is beneficial for improving the reaction rate, but excessively high temperatures will increase ammonia volatilization. Kinetic equilibrium is reached in approximately 3 hours. A suitable stirring rate ensures thorough solid-liquid mixing and eliminates external diffusion limitations.
[0017] Preferably, the stirring leaching temperature is 25-45℃, the stirring speed is 350rpm, and the time is 3-4h.
[0018] As a preferred embodiment of the present invention, in step 2, the solid-liquid separation method is filtration or centrifugation.
[0019] As a preferred embodiment of the present invention, in step 2, the calcium ion concentration of the leachate is ≤10mg / L.
[0020] Preferably, the leaching solution is used to recover copper using an extraction-electrowinning method, a displacement method, or a precipitation method.
[0021] As a preferred embodiment of the present invention, in step 2, the leaching residue contains ≥30wt% calcium carbonate and ≥4wt% silica.
[0022] Preferably, the leaching residue is sequentially washed with water, dried, and ball-milled to obtain raw materials for the preparation of building materials.
[0023] More preferably, the building material product is cement clinker, concrete admixture, non-fired brick, or geopolymer material.
[0024] The beneficial effects of this invention are: 1. Highly selective leaching: In the weakly alkaline ammonium carbonate-ammonia water system, copper is selectively dissolved in the form of copper-ammonia complex ions, with a copper leaching rate of over 70%; while calcium is hardly leached, fundamentally avoiding a series of problems such as calcium sulfate scaling, equipment blockage, and high acid consumption in the acid leaching process.
[0025] 2. No physical field enhancement required: Under the optimized leaching system, there is no need to introduce ultrasound or other technologies as required by existing technologies. This results in lower equipment investment, lower energy consumption, and easier industrial implementation.
[0026] 3. Direct application of leaching residue to building materials: Since phases such as calcium carbonate are completely preserved during the leaching process, the chemical composition of the leaching residue (high calcium, silicon content) is naturally suitable for building material production. It can be used directly as a building material raw material without complicated chemical conditioning or activation treatment, realizing full resource utilization.
[0027] 4. Simple process and low cost: Compared with acid leaching process (requires acid-resistant equipment and acid recovery system) and physical field strengthening process (requires ultrasonic generation equipment), the process of this invention is simple, the equipment is conventional, the investment is small, and the operating cost is low. Detailed Implementation
[0028] The claims of the present invention will be further described in detail below with reference to specific embodiments, but this does not constitute any limitation on the present invention. Any limited modifications made by any person within the scope of protection of the claims of the present invention are still within the scope of protection of the claims of the present invention.
[0029] Example 1 A selective ammonia leaching process for high-calcium copper ore tailings includes the following steps: Step 1: Take tailings from Baifang high-calcium copper mine (moisture content 6.15wt%, copper content 0.22wt%, calcium content 31.8wt%), grind it, and pass it through a 200-mesh sieve to obtain powder. Step 2: Add the powder, 1-octyl-3-methylimidazolium chloride and AEO-9 to the ammonium carbonate-ammonia water mixed leaching agent (ammonium carbonate concentration is 2.5mol / L, pH is 9.5), stir and leach for 3 hours at 25℃ and 350rpm, filter and separate to obtain leaching solution and leaching residue; The solid-liquid ratio of the powder and the ammonium carbonate-ammonia water mixed leaching agent was 1g:4mL, the mass of 1-octyl-3-methylimidazolium chloride was 0.05% of the mass of the powder, and the mass of AEO-9 was 0.05% of the mass of the powder. ICP analysis showed that Ca was not detected in the leachate (<0.1 mg / L), and the copper leaching rate was calculated to be 75.4%. The copper in the leachate can be further recovered using conventional extraction-electrowinning, displacement, or precipitation methods, which are well-known practices in the field and will not be described in detail here. The leaching residue (calcium carbonate content 34.6 wt%, silica content 5.2 wt%) was sequentially washed with water, dried at 105℃ to constant weight, and ball-milled (ball-to-material ratio 3:1, speed 75% of critical speed, time 30 min). The resulting powder was then mixed uniformly with P·O42.5 cement, standard sand, and deionized water at a mass ratio of 100:30:150:45, pressed into shape (molding pressure 20 MPa), and cured for 28 days to obtain unfired bricks. Testing showed that the compressive strength of the unfired bricks was 33.9 MPa, meeting the MU30 strength grade requirements in "Solid Concrete Bricks" (GB / T 21144). Leaching toxicity testing (TCLP method) showed that the leaching concentrations of heavy metals such as Cu, Pb, and Zn were all below the limits in GB 5085.3-2007.
[0030] Example 2 Based on Example 1, the leaching temperature in step 2 is changed to 45°C, while the other settings, parameters, and steps remain the same. Results: No Ca was detected in the leachate, and the concentration was still <0.1 mg / L. The copper leaching rate was calculated to be 79.5%, while the compressive strength of the unfired brick was 35.2 MPa.
[0031] Example 3 Based on Example 1, the ammonium carbonate concentration in step 2 was changed to 3 mol / L, the solid-liquid ratio was changed to 1 g: 3 mL, the leaching temperature was changed to 35 °C, and the leaching time was changed to 4 h, while the other settings, parameters, and steps remained the same. Results: The Ca ion concentration in the leachate was <0.5 mg / L, and the copper leaching rate was calculated to be 77.8%, while the compressive strength of the unfired bricks was 33.0 MPa.
[0032] Example 4 Based on Example 1, in step 2, the mass of 1-octyl-3-methyl imidazolium chloride is replaced with 1-decyl-3-methyl imidazolium chloride, the mass of AEO-9 is replaced with AEO-10, the solid-liquid ratio is changed to 1g:6mL, the leaching temperature is changed to 30℃, and the leaching time is changed to 6h. All other settings, parameters, and steps remain the same. Results: No Ca was detected in the leachate, and the concentration was still <0.1 mg / L. The copper leaching rate was calculated to be 78.4%, while the compressive strength of the unfired brick was 35.8 MPa.
[0033] Comparative Example 1 Based on Example 1, step 2 is changed to add the powder to 1.43 mol / L ammonia water at a solid-liquid ratio of 1g:4mL, stir and leach at 25℃ and 350rpm for 3h, filter and separate to obtain leachate and leach residue, and keep the other settings, parameters and steps the same. Results: Although Ca was not detected in the leachate (<0.1 mg / L), the calculated copper leaching rate was only 26.5%, which is not of great practical significance.
[0034] Comparative Example 2 Based on Example 1, in step 2, 1-octyl-3-methyl imidazolium chloride is replaced with AEO-9 by mass, while the rest of the settings, parameters and steps remain the same; Results: No Ca was detected in the leachate, and the concentration was still <0.1 mg / L. The copper leaching rate was calculated to be 71.9%, while the compressive strength of the unfired brick was 31.8 MPa.
[0035] Comparative Example 3 Based on Example 1, in step 2, AEO-9 is replaced with 1-octyl-3-methyl imidazole chloride, while the rest of the settings, parameters and steps remain the same. Results: No Ca was detected in the leachate, and the concentration was still <0.1 mg / L. The copper leaching rate was calculated to be 72.5%, while the compressive strength of the unfired brick was 32.2 MPa.
[0036] Comparative Example 4 Based on Example 1, in step 2, 1-octyl-3-methyl imidazolium chloride and AEO-9 are replaced by ammonium carbonate-ammonia water mixed leaching agent in equal mass, while the rest of the settings, parameters and steps remain the same. Results: No Ca was detected in the leachate, and the concentration was still <0.1 mg / L. The copper leaching rate was calculated to be 68.4%, while the compressive strength of the unfired brick was 29.4 MPa.
[0037] Comparative Example 5 Based on Example 1, in step 2, AEO-9 is replaced with AEO-7, while the other settings, parameters, and steps remain the same. Results: No Ca was detected in the leachate, and the concentration was still <0.1 mg / L. The copper leaching rate was calculated to be 73.3%, while the compressive strength of the unfired brick was 32.8 MPa.
[0038] Comparative Example 6 Based on Example 1, in step 2, AEO-9 is replaced with AEO-12, while the other settings, parameters, and steps remain the same. Results: No Ca was detected in the leachate, and the concentration was still <0.1 mg / L. The copper leaching rate was calculated to be 74.0%, while the compressive strength of the unfired brick was 33.2 MPa.
[0039] Based on the above results, the selective ammonia leaching process for high-calcium copper ore tailings provided by this invention has a high copper leaching rate. The resulting leaching residue can be directly used to prepare building materials without complex pretreatment, realizing the full resource utilization of high-calcium copper ore tailings and avoiding a series of problems such as scaling and corrosion that occur in acid leaching processes.
[0040] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, features in the embodiments of the present invention can be combined with each other unless otherwise specified.
Claims
1. A selective ammonia leaching process for high-calcium copper ore tailings, characterized in that: Includes the following steps: Step 1: Grind the high-calcium copper ore tailings to obtain powder; Step 2: Add the powder, imidazole ionic liquid and AEO surfactant to the leaching agent, stir and leach, separate the solid and liquid to obtain leachate and leaching residue.
2. The selective ammonia leaching process for high-calcium copper ore tailings according to claim 1, characterized in that: In step 1, the calcium content of the high-calcium copper ore tailings is not less than 25 wt% and the copper content is not more than 1 wt%.
3. The selective ammonia leaching process for high-calcium copper ore tailings according to claim 1, characterized in that: In step 2, the solid-liquid ratio of the powder and the leachate is 1g:2-6mL; the mass of the imidazole ionic liquid is 0.02-0.06% of the mass of the powder; and the mass of the AEO surfactant is 0.02-0.1% of the mass of the powder.
4. The selective ammonia leaching process for high-calcium copper ore tailings according to claim 1, characterized in that: In step 2, the imidazole-based ionic liquid is at least one of 1-octyl-3-methylimidazolium chloride, 1-decyl-3-methylimidazolium chloride, and 1-dodecyl-3-methylimidazolium chloride; and the average EO addition number of the AEO-based surfactant is 8-10.
5. The selective ammonia leaching process for high-calcium copper ore tailings according to claim 1, characterized in that: In step 2, the leaching agent is an ammonium carbonate-ammonia water mixed leaching agent; the ammonium carbonate concentration of the ammonium carbonate-ammonia water mixed leaching agent is 1.5-3.5 mol / L and the pH is 8.5-10.
5.
6. The selective ammonia leaching process for high-calcium copper ore tailings according to claim 1, characterized in that: In step 2, the stirring leaching temperature is 20-60℃, the stirring speed is 200-400rpm, and the time is 2-6h.
7. The selective ammonia leaching process for high-calcium copper ore tailings according to claim 1, characterized in that: In step 2, the calcium ion concentration of the leachate is ≤10mg / L.
8. The selective ammonia leaching process for high-calcium copper ore tailings according to claim 1, characterized in that: In step 2, the leaching residue has a calcium carbonate content of ≥30wt% and a silica content of ≥4wt%.
9. The selective ammonia leaching process for high-calcium copper ore tailings according to claim 8, characterized in that: The leaching residue is successively washed with water, dried, and ball-milled to obtain raw materials for the preparation of building materials.
10. The selective ammonia leaching process for high-calcium copper ore tailings according to claim 9, characterized in that: The building materials are cement clinker, concrete admixtures, non-fired bricks, or geopolymer materials.
Citation Information
Patent Citations
Copper mine tailing copper extraction method based on copper ammonia coordination-ultrasonic cooperation
CN121428287A